1996
DOI: 10.1007/s001289900024
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Change in Rat Testicular ATPase Activities in Response to HCH Treatment

Abstract: 1 HCH (Y-hexachlorocyclohexane), an organochlorine insecticide is used widely for agricultural and hygienic purposes in most of the developing countries including India. Like other organochlorine, HCH can also enter into the body by various means such as through food chain, through inhalation and through dermal contact. It has been reported that HCH preferably accumulates in adipose tissues and in membrane lipid layer (Zhu et al. 1986; Lopez-Aparicio et al.1 988). Besides exhibiting neurological (Woolley et a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The activity of Ca 2+ ATPase was assayed in the membrane fraction (10,000 × g pellet of the crude homogenate dissolved in the homogenizing buffer) according to the method of Roy and Chainy 20 . The samples (40 µg protein) were incubated in standard incubation medium consisting of 50 mM Tris-HCl, pH 7.4, 0.5 mM EGTA and 5 mM Ca 2+ .…”
Section: Methodsmentioning
confidence: 99%
“…The activity of Ca 2+ ATPase was assayed in the membrane fraction (10,000 × g pellet of the crude homogenate dissolved in the homogenizing buffer) according to the method of Roy and Chainy 20 . The samples (40 µg protein) were incubated in standard incubation medium consisting of 50 mM Tris-HCl, pH 7.4, 0.5 mM EGTA and 5 mM Ca 2+ .…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that methoxychlor and dichlorodiphenyltrichloroethane (DDT), but not lindane, induce sublethal changes in transmembrane potential, ROS production, and ATP-induced intracellular Ca 2ϩ homeostasis in bovine oviductal cells [43]. However, lindane and dieldrin stimulate ROS production in neutrophils by activating phospholipase A 2 [54], and lindane alters rat testicular Ca 2ϩ -and Mg 2ϩ -ATPase activities [55]. Perturbations in intracellular Ca 2ϩ homeostasis and in Ca 2ϩ uptake by mitochondria was also observed in rat cerebellar granule cells following PCB exposure [42,56].…”
Section: Organochlorines Affect Sperm Motility and Viabilitymentioning
confidence: 98%
“…Animals kom each group were sacrificed on the 46th day (onset of reproductive capacity) of age by decapitation (n = 5 for each parameter studied) and the testes were quickly dissected out, cleaned in normal saline (0.9%, w/v) solution and processed immediately for estimation of various oxidative stress parameters (Samanta & Chainy, 1997). Testicular mitochondria1 Ca2+-Mgz+-ATPase activity was estimated as described earlier (Roy & Chainy, 1996).…”
Section: Animals and Pesticide Treatmentmentioning
confidence: 99%
“…Earlier it was reported that hexachlorocyclohexane (HCH), an organochlorine pesticide, induces oxidative stress in the testis and the magnitude of induction is higher in the case of immature rats than the mature ones (Samanta & Chainy, 1997). Similarly, alteration in the mitochondrial ATPases of the rat testis to HCH is more pronounced in immature rats than their mature counterparts (Roy & Chainy, 1996). In the present study, in order to understand the impact of HCH exposure during critical stages of testicular development, rats were exposed to HCH during critical stages of sexual maturation (from 6 to 30 days of age) and changes in oxidative stress parameters and mitochondrial Ca2 +-Mg*+-ATPases in the testis were recorded on the 46th day (onset of reproductive capacity) of age.…”
Section: Introductionmentioning
confidence: 99%